A facile approach for preparing Zr-BDC and Zr-BDC-NH2 MOFs using solvothermal method. Issue 1 (1st June 2022) - Rahmidar, Lena; Gustaman Syarif, Dani; Suyatman,; Nugraha,
Abstract: In the last two decades, researchers have developed new compounds made of central metals that bond in coordination with organic ligands as linkers (for example, benzene-dicarboxylic acid or BDC). These compounds are called metal-organic frameworks (MOFs) which are also known as coordination polymer compounds. MOFs have large surface area and porosity so they can be used for various purposes, such as for adsorption and removal of hazardous materials of CO2 and Hg. Here, we proposed a facile solvothermal method for preparing two kinds of MOFs with Zr as a central metal, i.e. Zr-BDC and Zr-BDC-NH2. The synthesized MOFs were characterized using XRD, FTIR, SEM, TEM, and BET. The results show that both MOFs have a crystalline structure with cubic form on the surface of MOFs. Results of the FTIR analysis show the peak at 3400 1/cm that is due to the stretching of O-H bonds of both MOFs. In the Zr-BDC-NH2, peak at 1378 1/cm represents the stretching of N-H bonds in the amino benzene-dicarboxylic or terephthalic acid linker. The surface areas of Zr-BDC and Zr-BDC-NH2 MOFs are 714 and 757 m 2 /g, respectively. We will utilize these MOFs as a sensor for HER2 protein, a biomarker of breast cancer.